The Apoptotic Role of Metacaspase in Toxoplasma gondii - Li, Muzi; Wang, Hui; Liu, Jing; Hao, Pan; Ma, Lei; Liu, Qun (Frontiers in Microbiology, 2016)
Toxoplasma gondii is a major opportunistic pathogen that spreads in a range of animal species and human beings. Quite a few characterizations of apoptosis have been identified in T. gondii treated with apoptosis inducers, but the molecular mechanisms of the pathway are not clearly understood. Metacaspases are caspase-like cysteine proteases that can be found in plants, fungi, and protozoa in which caspases are absent. Metacaspases are multifunctional proteases involved in apoptosis-like cell death, insoluble protein aggregate clearance and cell proliferation. To investigate whether T. gondii metacaspase (TgMCA) is involved in the apoptosis of the parasites, we generated TgMCA mutant strains. Western blot analysis indicated that the autoproteolytic processing of TgMCA was the same as that for metacaspases of some other species. Indirect immunofluorescence assay (IFA) showed that TgMCA was dispersed throughout the cytoplasm and relocated to the nucleus when the parasites were exposed to the extracellular environment, which indicated the execution of its function in the nucleus. The number of apoptosis parasites was significantly diminished in the TgMCA knockout strain and increased in the TgMCA overexpression strain after treatment with extracellular buffer, as determined by the terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. The lack of TgMCA did not affect the parasite propagation in vitro and virulence in vivo, suggesting that it is probably redundant in parasite propagation. But overexpression of TgMCA reduced the intracellular parasites growth in vitro. The TgMCA knockout strain showed more viability in extracellular buffer compared to the parental and overexpression lines. In this study, we demonstrated that TgMCA contributes to the apoptosis of T. gondii.